Preservasi pengetahuan terhadap kegiatan katalogisasi literatur aksara Jawa di Perpustakaan Balai Bahasa DIY - Thoriq Tri Prabowo; Siwi Anjarwati; Mela Rosita (UIN Mataram, 2023)
Cataloging Javanese script literature is a specific skill that cannot be done by everyone or librarians. This study aims to describe the efforts to preserve knowledge and good practices in the cataloging activities at the Perpustakaan Balai Bahasa DIY. We collected qualitative data by interview, non-participant observation, and documentation to collect data. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The informants of this research are library coordinators and other related staff. The results of the study indicate that the preservation of tacit, explicit, and traditional knowledge is carried out at this institution. Knowledge preservation efforts need to be made into a structured activity so that the transfer of knowledge between librarians is more optimal.